1976
DOI: 10.1093/genetics/84.2.233
|View full text |Cite
|
Sign up to set email alerts
|

ORGANIZATION OF THE ROSY LOCUS IN DROSOPHILA MELANOGASTER: EVIDENCE FOR A CONTROL ELEMENT ADJACENT TO THE XANTHINE DEHYDROGENASE STRUCTURAL ELEMENT

Abstract: From a collection of electrophoretic variants of XDH obtained from laboratory strains and natural populations, a stock was isolated that was associated with much greater than normal levels of XDH activity. Preliminary recombination experiments demonstrated that this character maps to the rosy locus. While a series of observations failed to relate this phenotype to alteration in the structure of the XDH polypeptide, kinetic and immunological experiments did succeed in associating this character with variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(10 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Background: The fine-structure mating described in this report were designed to localize the site responsible for a two-fold increase in XDH levels detectable in strains bearing the r y f 4 isoallele (CHOVNICK et al 1976). Preliminary mapping experiments indicated that the site responsible for this increased activity (designated 2 0 9 ) resided in the 0.3 map unit interval from karriioisin to rosy, but at or to the left of all markers in the XDH structural element.…”
Section: The Selectiue Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Background: The fine-structure mating described in this report were designed to localize the site responsible for a two-fold increase in XDH levels detectable in strains bearing the r y f 4 isoallele (CHOVNICK et al 1976). Preliminary mapping experiments indicated that the site responsible for this increased activity (designated 2 0 9 ) resided in the 0.3 map unit interval from karriioisin to rosy, but at or to the left of all markers in the XDH structural element.…”
Section: The Selectiue Systemmentioning
confidence: 99%
“…During the fine-structure mapping of a putative xanthine dehydrogenase regulatory element (CHOVNICK et al 1976), one series of crosses afforded an opportunity to detect some of these unusual events. In particular, triploid and partially trisomic individuals (these latter bearing tandem direct duplications of the rosy region) were recovered at unexpectedly high frequencies.…”
mentioning
confidence: 99%
“…Selective screens have been available to recover regulatory mutations at the rosy (xanthane dehydrogenase), adh (alcohol dehydrogenase), and rudimentary (carbamylphosphate synthetase [CPSase]-aspartate transcarbamylase [ATCase]-dihydroorotase [DHOase]) loci; however, no regulatory mutations have been recovered in screens with conventional mutagens such as ethyl methanesulfonate (EMS) and X-rays. In fact the only putative control mutations at these loci have been isolated either from natural populations (6,33) or as spontaneous mutations (35). Hence, it could be argued that control regions of Drosophila genes and perhaps genes of other eucaryotes may be refractory to many of the standard mutagens and that it would be worthwhile employing a somewhat different approach for the generation of regulatory mutations.…”
mentioning
confidence: 99%
“…This locus is an appropriate one to screen for evidence of loci affecting protein mobility. There is evidence for a cis-acting control site (i409) for Xdh immediately to the left of the structural gene (CHOVNICK et al 1976;MCCARRON et al 1979). In addition three other loci, low xanthine dehydrogenase (Jxd, 3-33.9), maroon-like (ma-I, 2-64.8) and cinnamon (cin, 1-0.0) also affect XDH activity (MACINTYRE and O'BRIEN 1976).…”
mentioning
confidence: 99%